REVIEW ARTICLE: ENERGY SAVING AND EFFICIENCY METHODS IN PETROCHEMICAL INDUSTRY - Devania Helena Kharisma Triaji (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2021)
Energy Saving and Efficiency Methods in the Petrochemical Industry are indispensable for the petroleum industry. Energy saving and efficiency is now recognized as the most important goal worldwide. Therefore, it is currently common to combine traditional mechanism methods based on momentum transport, energy transport, quality transport (TT) and reaction engineering (RG) (TT-RG), with data-driven artificial intelligence methods. The aim is to achieve production optimization and energy savings. By streamlining and saving energy in the petrochemical industry, we can take petroleum and petrochemicals in a more advanced and efficient direction. The methods that can be used are AP based mechanism method, TT-RG, data-based artificial intelligence method, and hybrid method which combines mechanism and data-driven. For the most appropriate method, we can choose according to our needs by weighing the advantages and disadvantages of each method. Finally, the future development direction for energy efficiency evaluation in complex petrochemical industries is given.